« L’épopée » des clandestins - Zied Hadfi (Conserveries Mémorielles)
This work builds on a qualitative survey on illegal migration, conducted with thirty Tunisian illegal immigrants in France, essentially in the Paris region. Here, we find real life stories of migrants recounted by their own words. Referring to descriptive sociology, we try to reconstruct the routes sociologically, to profile actors and trace back networks of immigration and describe the spatial and social practices resulting from them. The survey takes various Then from an external angle, we will deal with globalization that has opened new horizons and ambitions among some youth lured by the mirage of Europe. We are interested obviously to highlight this new culture of migration, based on the dream, the fascination and idealization, nurtured and maintained daily by the illusion and false advertisements. We will identify the act of migration in its entirety, wherever it occurs in time and space by social actors (illegal immigrants) as a turning point that results in a "hijra" (emigration), by both the mind and body. Qualitative research techniques, particularly the exploration rather than participatory observation. Varied and moving stories which emphasize the individuality of the narrator in a very unusual way. Each individual speaks as an affirmed « I » and tells a very powerful and dramatic crucial moment in « his » history. The texts produced by the respondents show a link between the first-person singular and the first in the plural (we). Here the interviewee is speaking for the entire community of illegal immigrants, describing their suffering, their fear, but also their hopes and their success. Through sequencing of various pronominal forms "they", "we", « them" ... We were able to approach the topic studied from various angles "internal" and "external". We propose here to examine the local component of this phenomenon, focusing on understanding the factors (push / pull) that have driven these illegal migrants out of home countries. Kicking in, sometimes, suicidal adventures where they are told that the land flowing with milk and honey, starting from the countries that are still not at the status of "International beggars ». In fact, they burn the borders practicing "Harga". We seek to highlight their vulnerable situation while describing the dangers hanging over them and fears that inhabit them, and highlighting their anticipation and hope for the future.